2022
DOI: 10.3389/fphys.2022.960580
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cinnamon supplementation on glycolipid metabolism in T2DM diabetes: A meta-analysis and systematic review

Abstract: Background: Cinnamon is a spice used in cooking and in large quantities as a medical complement with hypoglycemic and lipid-lowering properties. The potential pharmacological mechanisms underlying cinnamon’s anti-diabetic properties and its active ingredients have not been adequately determined. The current meta-analysis aims to systematically review the potential pharmacological mechanisms underlying the hypoglycemic and hypolipidemic efficacy of cinnamon administration and summarize clinical recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
8
0
2
Order By: Relevance
“…Nearly 16 randomized controlled trials including more than one thousand patients reported that cinnamon had the potential of regulating glucose metabolism and showed improvement in blood glucose parameters both random and fasting. These trials had also concluded that cinnamon can reduce insulin resistance and associated symptoms (Zhou et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 16 randomized controlled trials including more than one thousand patients reported that cinnamon had the potential of regulating glucose metabolism and showed improvement in blood glucose parameters both random and fasting. These trials had also concluded that cinnamon can reduce insulin resistance and associated symptoms (Zhou et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…2023;44:e20230051 na sinalização da insulina e na regulação da dislipidemia. Isto é, o uso dessa fitoterapia é útil na complementação dos esquemas terapêuticos aos pacientes com diabetes (13) .…”
Section: Discussionunclassified
“…Dentre os fitoterápicos que se destacam e vêm ganhando força como adjuvante no tratamento dos pacientes com quadros de desregulação metabólica, evidencia-se a canela. Uma recente metanálise mostrou que a canela tem influência significativa na regulação do metabolismo glicolipídico, podendo ser utilizada, com segurança, como adjuvante em pacientes com diabetes (13) . Todavia, estudos que considerem a efetividade da canela como hipolipemiante em pacientes com diabetes, em especial, na população brasileira, ainda são escassos, suscitando a necessidade de novas investigações sobre o tema.…”
Section: Introductionunclassified
“…Cinnamon is used as a spice worldwide. Aqueous or ethanol extracts of cinnamon have been shown to exert anti-DM effects in several preclinical and clinical investigations ( Mang et al, 2006 ; Qureshi et al, 2019 ; Zhou et al, 2022 ). Diverse species of cinnamon have been reported to have different hypoglycemic effects ( Lu et al, 2011 ), but their constituents and underlying molecular mechanism of action are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%